Delivering Endothelial Keratoplasty Grafts: Modern Day Transplant Devices. (3rd April 2022) - Parekh, Mohit; Romano, Vito; Hassanin, Kareem; Testa, Valeria; Wongvisavavit, Rintra; Ferrari, Stefano; Willoughby, Colin; Ponzin, Diego; Jhanji, Vishal; Sharma, Namrata; Daniels, Julie; Kaye, Stephen B.; et al.
ABSTRACT: Purpose: To summarize the graft loading, transporting and delivery devices used for endothelial keratoplasty (EK). Methods: A literature search of electronic databases was performed. Results: New techniques and devices have been introduced and implemented to prepare, load, transport and transplant the grafts for EK. The advantages are not only limited to the surgical theatre but also widely spread across the eye banking field. Investigation of advanced materials and designs have been rapidly growing with continuous evolution in the field of eye banking and corneal transplantation. Innovative techniques and modern devices have been evaluated to reduce the endothelial cell loss and increase the precision of the transplant in order to benefit both surgeons and the patients. Conclusions: It is extremely important to reduce any potential wastage and optimize the use of every available donor cornea due to the limited availability of healthy cadaveric donor corneas required for transplants. As a result, the use of pre-cut and pre-loaded grafts supplied by the eye banks in calibrated devices have been gaining momentum. Innovation in the field of bioengineering for the development of new devices that facilitate excellent clinical outcomes along with reduction in learning curve has shown promising results.